Justiça restaurativa: ampliando suas fronteiras para o direito de família - SOARES, Cynthia Fernanda Oliveira (Universidade Federal do Pará, 2023)
Family conflicts are complex and are growing in scale related to several aspects, such as psychological, behavioral, moral, cultural and economic, leading to the massification of judicialization due to the actors involved not being able to reach a consensual resolution. This fact also generates the possibility of other conducts arising from the absence of this consensus with consequences, including criminal ones. This research aimed to verify the possibility of applicability of Restorative Justice in conflicts of Family Law whether judicial or not, observing its specificities so that the methodological approach could be applied satisfactorily. As a methodology, qualitative empirical research with a hermeneutic focus was chosen. In the phase of restorative justice interventions in concrete cases, the peacebuilding circle method was applied, according to the methodology described by Pranis (2011). First, a bibliographic documentary survey was carried out on restorative justice, family conflicts, restorative practices, projects and legislative policy. Then, the choice of cases for interventions to be carried out, with cases of family conflict that were under the responsibility of the Nucleus of Legal Practice (NPJ) of the Federal University of Pará (UFPA) being selected; the Court of Justice of the State of Pará (TJPA) of Belém, through the 4th and 5th Family Courts; Permanent Nucleus of Consensus Methods for Conflict Resolution (NUPEMEC), and the Judiciary Center for Conflict Resolution and Citizenship (CEJUSC) of the Capital and Ananindeua, totaling 14 interventions. Which followed the following steps: pre-circle, peace-building circle and post circle, when possible. After analyzing the interventions, the results were: five fully restorative cases; four partially restorative cases; and five non-restorative cases. Given the above, it is observed that the resolution of family conflicts through Restorative Justice is fully possible and even recommendable, providing the actors involved with the opportunity to reach a consensual, humanized and democratic solution, based on dialogue and active listening , enabling a safe environment for the discussion of difficult and painful matters that meets the needs of the parties, generating obligations in relation to the damage caused, making them assume their responsibilities.